A chromenone analog as an ATP-competitive, DNA non-intercalative topoisomerase II catalytic inhibitor with preferences toward the alpha isoform. Issue 85 (10th October 2019) - Park, Seojeong; Hwang, Soo-Yeon; Shin, Jaeho; Jo, Hyunji; Na, Younghwa; Kwon, Youngjoo
Abstract : Compound 52 exhibited highly topo IIα-selective properties as an ATP competitive catalytic inhibitor with less toxicity, unlike topo II poisons. Abstract : 5-Hydroxy-2-phenyl-7-(thiiran-2-ylmethoxy)-4 H -chromen-4-one (compound 52 ) was found as a DNA non-intercalative topo II specific catalytic inhibitor by targeting its ATP-binding domain. Showing changes in interaction with Mg 2+, it exhibited highly selective properties against the α-isoform with less toxicity, unlike other topo II poisons, such as etoposide.